Kandungan Mioglobin dan Warna pada Ikan Tuna (Thunnus albacares) Loin yang Diaplikasi dengan Gas Non Kondensat - Cindy R M Loppies; Beni Setha; Ruslan H S Tawari; Febby J Polnaya; Joseph Pagaya; Antho N Siahaya (AGRITEKNO: Jurnal Teknologi Pertanian, 2025)
The use of carbon monoxide gas in handling export-quality tuna loins gas has been prohibited by the FDA due to its residual effects. As an alternative, filtered smoke derived from the combustion of hardwood has been proposed. However, this gas is expensive and primarily produced in Hawaii. During the production of liquid smoke, a non-condensable gas is generated that contains carbon monoxide and may serve to preserve quality, including color and myoglobin content. The aim of this research was to identify the components of non-condensable gas and evaluate its application on tuna loins. A descriptive method was employed, and the data were presented in images and tables. The materials used included sago waste (waa sagu) and tuna loins (Thunnus albacares). Observations involved analyzing the composition of the non-condensable gas from sago waste, as well as changes in color and myoglobin content of tuna loins treated with the gas. The analysis identified 12 components in the non-condensable gas, including nitrogen and carbon monoxide. Tuna loins treated with this gas maintained a red color and a myoglobin content of 49.31±0.70 mg %.